The integrating role of higher public education with middle school: actions and projects in the north of Estado do Espírito Santo (ES), Brazil (Research, Society and Development, 2019)
The INEP census of 2015 shows that 3 out of 20 schools in Espírito Santo have a science laboratory. The lack of interaction between the students and the applications of the science subjects they study in the books reflects in the grades obtained in exams (national and international) which evaluate their performance in this field of knowledge. A project that brings students from public schools and undergraduate students together in order to cultivate microalgae – from the construction of a photo bioreactor with recyclable materials to the extraction of the microalgae oil – can change this situation. Reviewing the studies on microalgae developed in the Laboratório de Engenharia do Trabalho and in the Laboratório de OperaçõeUnitárias at the Centro UniversitárioNorte do Espírito Santo (CEUNES) between 2012 and 2014, the benefits and challenges to implement such project were identified.